1993
DOI: 10.1128/mcb.13.9.5524
|View full text |Cite
|
Sign up to set email alerts
|

Identification and purification of a protein that binds DNA cooperatively with the yeast SWI5 protein.

Abstract: The Saccharomyces cerevisiae SWI5 gene encodes a zinc finger protein required for the expression of the HO gene. A protein fusion between glutathione S-transferase and SWI5 was expressed in Escherichia coli and purified. The GST-SWI5 fusion protein formed only a low-affinity complex in vitro with the HO promoter, which was inhibited by low concentrations of nonspecific DNA. This result was surprising, since genetic evidence demonstrated that SWI5 functions at the HO promoter via this site in vivo. A yeast fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 50 publications
2
62
1
Order By: Relevance
“…PCR reactions were performed as described above using the labeled oligonucleotides as primers and plasmids containing the appropriate ADE5,7 sequences as templates to amplify the region between Ϫ211 and Ϫ145 (relative to the ADE5,7 start codon). The templates were pR224, carrying the wild-type ADE5,7 fragment, or selected plasmids carrying mutated ADE5,7 promoter fragments, constructs numbered 5,7,10,11,13,14,19,20,27,29,34,35,39, and 43 as listed in Table IV. After PCR, a portion of each sample was separated by electrophoresis, and concentrations of the PCR products were estimated by ethidium bromide staining in comparison with known concentrations of duplex oligonucleotides of approximately the same length.…”
Section: ј-Cgtcagatctgccccgnnngtagtgac-3јmentioning
confidence: 99%
See 3 more Smart Citations
“…PCR reactions were performed as described above using the labeled oligonucleotides as primers and plasmids containing the appropriate ADE5,7 sequences as templates to amplify the region between Ϫ211 and Ϫ145 (relative to the ADE5,7 start codon). The templates were pR224, carrying the wild-type ADE5,7 fragment, or selected plasmids carrying mutated ADE5,7 promoter fragments, constructs numbered 5,7,10,11,13,14,19,20,27,29,34,35,39, and 43 as listed in Table IV. After PCR, a portion of each sample was separated by electrophoresis, and concentrations of the PCR products were estimated by ethidium bromide staining in comparison with known concentrations of duplex oligonucleotides of approximately the same length.…”
Section: ј-Cgtcagatctgccccgnnngtagtgac-3јmentioning
confidence: 99%
“…The results of electrophoretic mobility shift assays suggested that BAS2 binds to the ADE2 and ADE5,7 promoters; however, no specific binding sites were identified (3). In addition to participating with BAS1 in transcriptional activation of HIS4 and the ADE genes, BAS2 (also known as PHO2 and GRF10) stimulates transcription of PHO5 (12) and HO (13). High level transcription of HO requires BAS2 in conjunction with SWI5 (13,14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, cleavage by thrombin releases the DNA-binding protein (17). The GST fusion protein system was successfully used to determine the DNA-binding sites for a number of proteins such as SWI5 in yeast (18), N-Myc in mouse (19), and T/E1A in human (20). In A. nidulans, binding sites for the CreA repressor (16) and NirA (21) and UaY (6) activators have been localized using GST fusion proteins.…”
mentioning
confidence: 99%